The Role of Peer Group Communication in Shaping Lifestyle and Behavior of Migrant University Students - Dea Ananda; Hanum Dwi Lestari; Tiara Anggraini; Sri Narti (Multidisciplinary Journals, 2026)
Migrant university students experience major social and behavioral changes as they transition into independent living away from parental supervision. During this period, peer group communication becomes a central factor influencing students’ perceptions, attitudes, and daily behaviors. Informal interactions among peers, such as social gatherings, leisure activities, and everyday conversations, serve as important channels through which values and lifestyle norms are shared and reinforced. This study aims to examine the role of peer group communication in shaping the lifestyle and behavior of migrant university students, particularly in relation to social adjustment, financial practices, and academic engagement. This research employs a qualitative descriptive approach using content analysis of six news articles that report on the lived experiences of migrant students in Bengkulu. The analysis focuses on communication patterns within peer groups and the behavioral responses that emerge from continuous social interaction. The findings indicate that peer communication strongly influences students’ understanding of social acceptance and freedom, often encouraging conformity to group norms. In many cases, this results in increased consumptive behavior, reduced self-regulation, and declining academic performance due to social pressure. However, the study also reveals that peer communication can generate positive outcomes when group interactions promote supportive and reflective dialogue. In such environments, students demonstrate improved adaptability, emotional awareness, and responsible decision-making. Overall, peer group communication plays a dual role as both a source of social pressure and a medium for personal development among migrant university students.